Obtenção de nanoamido de amêndoa de manga e sua aplicação em filmes de amido para embalagens de alimentos - Oliveira, Ana Vitória de (2016)
Mango processing generates tons of by-products (peels, seed coats and kernels) corresponding to 40-45 wt% of fruit, and have high potential added value. The seed kernels represents 13% of that weight, and is mainly composed of starch (50%), which can be extracted and used for food packaging or coating. Despite its appeal related to renewability and biodegradability, starch films still have limitations on their barrier and mechanical properties. Starch nanocrystals (SNC) may be incorporated as a reinforcement phase in order to improve such characteristics. The objective of this study was to develop bionanocomposite films from mango kernel starch reinforced with different contents of starch nanocrystals obtained by acid hydrolysis and ultrasonication, and to compare them with those films obtained from commercial maize starch. Starches and SNC were submitted to chemical, morphological, and thermal characterizations. The films were prepared with different concentrations of SNC (0-10 wt% on the starch matrix) and characterized by tensile properties, opacity and water vapor permeability (WVP). The starch extracted from kernels presented a high yield (38.5%), low levels of impurities, a reasonable amylose content (22.1%), type A crystallinity, ellipsoidal granules with an average size of 13.2 μm, and gelatinization temperature between 75.66 and 84.13° C. The SNC were stable in solution (zeta potential > 25 mV - module), with sizes around 79 nm, high-yield (31.7%), and higher thermal stability than native starch. SNC addition resulted in improved tensile strength and modulus, higher opacity, and lower elongation at break. The films presented properties comparable to those of comercial starch, with highertensile strength, modulus, and opacity.